Implikasi Hermeneutika dalam Reinterpretasi Teks-teks Hukum Islam - Ahmad Hasan Ridwan (Al 'Adalah: Jurnal Hukum Islam, 2017)
Abstract: The Contribution of Hermeneutics in re-Interpreting Islamic Legal Texts.  This article examines the contribution of Hermeneutics in reinterpreting the Islamic legal texts. Hermeunetcs enters the treasures of Islamic law through active dialogs between Muslim and Western scholars, and later It becomes an integral part of the of religious  discourse in understanding religious texts critically. Among a number of Muslim exponents actively offering new models of interpretation are Sayhrur and Abu Zaid. Shahrur, with the his boundary limit theory, and Abu Zaid, with his significance of intelectual meaning theory,  have inspired Muslims to initiate the reform movement of thought as a critical response to the discourse of Islamic law. In the model of this new legal interpretation, hermeneutics becomes an alternative method when the traditional interpretation of Islamic legal thought fails to understand contemporary reality through the interpretation of legal texts.